2014
DOI: 10.1002/psc.2703
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of continuous B‐cell epitopes in the N‐terminus of glutamate decarboxylase67 using monoclonal antibodies

Abstract: Glutamate decarboxylase (GAD) is an autoantigen associated with the autoimmune disorders Type-1 diabetes (T1D) and stiff-person syndrome (SPS). The protein, being an essential enzyme involved in the production of the inhibitory neurotransmitter γ-aminobutyric acid, exists in two isoforms, GAD67 and GAD65. Both isoforms may be targeted by autoantibodies in SPS and T1D patients, although SPS primarily is associated with the presence of GAD67 autoantibodies, whereas T1D mainly is associated with the presence of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 55 publications
6
19
0
Order By: Relevance
“…This technique is still the major method for MAb production, as described by Köhler and Milstein, even though minor modifications may be introduced, mainly in the screening phase, where an assay system identical to the end stage use should be used to avoid selection of clones with aberrant properties [94]. Upon successful screening and cloning, highly specific MAbs are obtained and the epitopes of these can be characterised with high precision, as illustrated by recent studies of MAbs to the glutamate decarboxylase isoforms 65 and 67, which were shown to recognise linear epitopes located in flexible structures [47,95]. Similar results have been obtained with many other MAbs, which verifies the stringent requirements for an optimal antibody-antigen interaction [33,46,96,97].…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique is still the major method for MAb production, as described by Köhler and Milstein, even though minor modifications may be introduced, mainly in the screening phase, where an assay system identical to the end stage use should be used to avoid selection of clones with aberrant properties [94]. Upon successful screening and cloning, highly specific MAbs are obtained and the epitopes of these can be characterised with high precision, as illustrated by recent studies of MAbs to the glutamate decarboxylase isoforms 65 and 67, which were shown to recognise linear epitopes located in flexible structures [47,95]. Similar results have been obtained with many other MAbs, which verifies the stringent requirements for an optimal antibody-antigen interaction [33,46,96,97].…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…Amino acid composition Hydrophilic aas, charged aas, Pro, Gly (represented in loops) [33,138] Peptide length 8-25 aa [46,130,[132][133][134] Peptide structure Linear, flexible, cyclic, loops, turns, helices [25,86,87,[93][94][95] Protein target Accessible epitope, areas of high conservation, areas of hypervariability, N/C-termini, post-translational modifications [128,129,138] Following peptide synthesis, the peptides are conjugated to carriers to ensure immune responses with high antibody titres, since many peptides are not immunogenic by themselves. Traditional carriers include bovine serum albumin, keyhole limpet hemocyanin, and ovalbumin [45,128,[139][140][141].…”
Section: Selecting Factors Examples Referencesmentioning
confidence: 99%
“…The majority of epitopes are composed of 8–12 aas [1,2,3,4,5,6]. Except from antibodies recognizing modified epitopes, are epitopes seldom shorter than 6 aas, as antibody-antigen interactions depend on several aas for a stable interaction [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, when the GAD67/65 fusion protein was expressed in plants it was localized predominantly in the cytosol . A truncated version of GAD65mut would be preferable to a fusion protein for diagnostic and therapeutic applications to avoid cross‐reaction with autoantibodies against GAD67, which are not produced in diabetes but are relevant in other autoimmune diseases such as stiff‐person syndrome .…”
Section: Discussionmentioning
confidence: 99%
“…We previously described the cytosolic targeting of GAD65 in plants by replacing the N‐terminus of the protein with the homologous region of GAD67, the hydrophilic isoform of GAD . However, the N‐terminal region of GAD67 contains epitopes representing stiff‐person syndrome, another autoimmune disease , and this could interfere with the diagnosis and treatment of T1D. We therefore evaluated three N‐terminal deletions of GAD65mut as a strategy to prevent its association with membranes in plant cells.…”
Section: Introductionmentioning
confidence: 99%